2009
DOI: 10.1007/s00435-009-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing and arm regeneration in Ophioderma longicaudum and Amphiura filiformis (Ophiuroidea, Echinodermata): comparative morphogenesis and histogenesis

Abstract: All species of the Ophiuroidea have exceptional regenerative capabilities; in particular, they can replace arms lost following traumatic or self-induced amputation. In order to reconstruct this complex phenomenon, we studied arm regeneration in two diVerent ophiuroids, Ophioderma longicaudum (Retzius, 1805) and Amphiura Wliformis O. F. Müller, 1776, which are quite distantly related. These species present contrasting regeneration and diVerentiation rates and diVer in several ecological traits. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 34 publications
(49 reference statements)
4
74
1
1
Order By: Relevance
“…Based on histological studies, Wood et al (Wood et al, 2008) suggested that unfed A. filiformis increases protein metabolism by the breakdown of muscle tissues to fuel increased energetic demands in response to seawater acidification. It is likely that enhanced catabolism and cell turnover/dedifferentiation of muscle tissues following traumatic amputation in brittlestars and crinoids is related to cell differentiation to produce stem cells to regenerate lost tissues rather that fueling calcification processes (Candia Carnevali and Bonasoro, 2001;Biressi et al, 2010). However, despite increased NH 4 + excretion rates, the present study could not demonstrate any changes in ratios between ADM and DM between pH treatments, which would have indicated an increased utilization of muscle tissue or other amino acid compounds as an energy source.…”
Section: Research Articlecontrasting
confidence: 69%
“…Based on histological studies, Wood et al (Wood et al, 2008) suggested that unfed A. filiformis increases protein metabolism by the breakdown of muscle tissues to fuel increased energetic demands in response to seawater acidification. It is likely that enhanced catabolism and cell turnover/dedifferentiation of muscle tissues following traumatic amputation in brittlestars and crinoids is related to cell differentiation to produce stem cells to regenerate lost tissues rather that fueling calcification processes (Candia Carnevali and Bonasoro, 2001;Biressi et al, 2010). However, despite increased NH 4 + excretion rates, the present study could not demonstrate any changes in ratios between ADM and DM between pH treatments, which would have indicated an increased utilization of muscle tissue or other amino acid compounds as an energy source.…”
Section: Research Articlecontrasting
confidence: 69%
“…Immune cells with phagocytic potential have been identified across the invertebrates, e.g. within Arthropoda [81] and Echinodermata [89]. During wound repair, after clot formation, specialized immune cells infiltrate the wound site and phagocytose cell debris and foreign organisms [90].…”
Section: (Iii) Clot Formationmentioning
confidence: 99%
“…During wound repair, after clot formation, specialized immune cells infiltrate the wound site and phagocytose cell debris and foreign organisms [90]. Infiltrated cells then proliferate, forming granulation tissue, which consists of multiple cell types, collagen and a basic ECM, and provides a platform for re-epithelialization [81,89]. Although there are differences among species, these cellular phases of wound healing have been documented within numerous invertebrates [81,91].…”
Section: (Iii) Clot Formationmentioning
confidence: 99%
“…Histological studies have divided arm regeneration in brittle stars into 4 main phases: wound repair with re-epithelialisation; early regeneration with complete healing and cell proliferation at the site of damage; intermediate regeneration resulting in blastema formation; and, finally, advanced regeneration with the development of a miniature arm (Biressi et al 2010). Based on gross morphological observations, it is production of a regenerative bud and arm elongation that constitutes the delayed phase in Ophionotus victoriae (Clark et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, regeneration in the temperate brittle star Ophioderma longicaudum has been described to have an even slower regeneration rate of 0.17 mm wk −1 ; although, it took only 3 wk to initiate regeneration and generate a blastema and measureable regenerative bud (Biressi et al 2010). Here we describe further regeneration studies on another common Antarctic brittle star, Ophiura crassa Mortensen, 1936, to further elucidate regeneration processes in ophiuroids and in particular to understand the effect of temperature.…”
Section: Introductionmentioning
confidence: 99%